Laboulbeniomycetes: Evolution, natural history, and Thaxter's final word - Blackwell, Meredith; Haelewaters, Danny; Pfister, Donald H (Mycologia, 2020)
Historically, thallus-forming Laboulbeniomycetes, including the orders Laboulbeniales and Herpomycetales, were set apart because of their distinctive morphology and ecology. Although some biologists correctly interpreted these arthropod ectoparasites as fungi, even ascomycetes, others thought they were worms, red algae, or members of taxa described especially for them. Speculation on the evolution of the group involving red algae, the morphology-based Floridean Hypothesis, persisted deep into the 20th century, in part because valid alternatives were not presented. Although the distinctive features of Laboulbeniales clearly set them apart from other fungi, the difficulty was in the absence of characters grouping them among the fungi. Thaxter considered the Laboulbeniales to be ascomycetes, but he avoided phylogenetic discussions involved in the Floridean Hypothesis all of his life. Eventually, developmental studies of the life history of Pyxidiophora species, hyphal perithecial ascomycetes with 2-celled ascospores, revealed characters connecting Laboulbeniales to other ascomycetes. The distinctive morphological features of Laboulbeniales (absence of mycelium, a thallus developed from 2-celled ascospores by cell divisions in several planes, arthropod parasitism) can be best understood by comparison with Pyxidiophora. The development of a 3-dimensional thallus composed of true parenchyma occurs not only in Laboulbeniales, but also in Pyxidiophora species. The life history of arthropod ectoparasitism of Laboulbeniales as well as mycoparasitism and phoretic dispersal by arthropods of Pyxidiophora species can be explained by Tranzschel's Law, originally applied to rust fungi. Molecular analyses including other arthropod-associated fungi have contributed to a better understanding of an enlarged class, Laboulbeniomycetes, which now includes a clade comprising Chantransiopsis, Tetrameronycha, and Subbaromyces. A two-locus phylogenetic tree highlights evolutionary and life history questions with regard to the placement of Herpomycetales as the first diverging lineage of the Laboulbeniomycetes. The sister group for all the Laboulbeniomycetes remains to be discovered.
Keywords: molekulární evoluce; Ascomycota; Laboulbeniopsis; Pyxidiophora; Coreomycetopsis; Kathistes; Chantransiopsis; Subbaromyces; Animals; mykózy; zvířata; Laboulbeniales; fylogeneze; Mycoses; členovci; Arthropod-associated fungi; phylogeny; Arthropods; Tetrameronycha; Phylogeny; Evolution, Molecular